Addition of HO‐Acids to N, N‐Bis(oxy)enamines: Mechanism, Scope and Application to the Synthesis of Pharmaceuticals. Issue 41 (7th November 2017) - Naumovich, Yana A.; Golovanov, Ivan S.; Sukhorukov, Alexey Yu.; Ioffe, Sema L.
Abstract : The regioselectivity of the addition of HO‐acids to the activated π bond in N, N ‐bis(oxy)enamines has been found to be dramatically dependent upon the solvent. Mechanistic investigations and quantum‐chemical calculations revealed that solvent affects the reaction pathway. In basic solvents (DMF, NMP, DMSO), N, N ‐bis(oxy)enamines were converted into nitrosoalkenes by a Lewis base promoted process followed by oxy‐Michael addition of the HO‐acid. In non‐polar solvents (toluene, CH2 Cl2 ), the reaction occurs by an acid‐promoted SN ′ substitution of the N ‐oxy‐group via a highly reactive N ‐vinyl‐ N ‐alkoxynitrenium species. Based on these studies, general and efficient protocols for the oximinoalkylation of various HO‐acids (carboxylic acids, phenols, hydroxamic, phosphoric and sulfonic acids) employing readily available N, N ‐bis(oxy)enamines were developed. These methods proved to be applicable to the post‐modification of natural molecules bearing acidic OH groups (such as steroidal hormones, bile acids, protected amino acids and peptides) and ligands (BINOL). The resulting α‐oxyoximes were demonstrated to be useful precursors of valuable 1, 2‐amino alcohol or 1, 2‐hydroxylamino alcohol derivatives, including the antiarrhythmic drug Mexiletine and a potent matrix metalloproteinase inhibitor. Abstract : The reactivity of N, N ‐bis(oxy)enamines towards HO‐acids has been found to be divergent and dramatically dependent upon the solvent, which affects the reaction pathway.